Collaborative Group Investigation and Self Efficacy on Pre-Service Science Teachers’ Critical Thinking Skills - Sukardi Abbas*; Wirda Az Umangap; Astuti Muh Amin (Jurnal Pendidikan Sains Indonesia, 2023)
In order to teach future generations, preservice science teachers must possess critical thinking skills. However, relatively few studies have examined these skills at the tertiary level, particularly in elementary school science teacher education departments. This study sought to determine the effect of collaborative group investigation (CGI) learning and self-efficacy on the critical thinking skills of students. With a non-equivalent control group design and a 2 x 2 ANOVA inferential statistical test, a quasi-experimental design was implemented. The subjects of this study were forty science teacher candidates who took the Environmental course at a university in Indonesia. A self-efficacy questionnaire and a test of critical thinking skills constituted the research instruments. The results indicated that the collaborative group investigation group received an average score of 62.2, whereas the direct learning group received an average score of 48.8, with an Fcalculated of 87.626 and a significance value of 0.000. The data analysis revealed substantial differences between the collaborative group inquiry group and the direct learning group in terms of critical thinking skills.  The interplay between learning strategies and self-efficacy affects the critical thinking skills of pupils because collaborative learning practices can engage students actively through teamwork, idea exchange, decision making, and shared responsibilities